Serotype distribution of pneumococci isolated from pediatric patients with acute otitis media and invasive infections, and potential coverage of pneumococcal conjugated vaccines - Reijtman, Vanesa R (2013)
Fil: Reijtman, Vanesa R. Servicio de Microbiología, Hospital de Pediatría, Ciudad Autónoma de Buenos Aires; Argentina.